(untitled) (Estudios Sociales, 2022)
The objective of this article is to offer a journey through the trajectory of those who occupied the highest institutionalized positions within the radical governments in the province of Córdoba during the hegemony of the Radical Civic Union at the head of the executive of the province that spanned the period 1983 -1999. Based on diverse information, we propose a socio-demographic and political reconstruction of the profiles of the ministers, starting from the consideration that long-term social patterns can be identified in their appointment together with other more conjunctural ones typical of the specific political scenarios. The latter are the ones that generate the social conditions of access to the cabinet. In this way, it is expected to contribute to the understanding of the selection mechanisms of state constituencies in particular and of political practices in general.